Social and digital vulnerabilities: The role of participatory processes in the reconfiguration of urban and digital space - Antonucci, Maria Cristina; Sorice, Michele; Volterrani, Andrea (Frontiers in Political Science, 2022)
In the Italian context, political and social participation in the urban dimension has experienced innovations to broaden the inclusion of citizens in public choices relating to citylife and to urban renovation . Participation found in the city a relevant space to experiment with innovation in the relationship between institutions and citizens, Many initiatives advanced and developed over the years have had a powerful lever in technology: participatory budgets, consultations, public-private-non-profit partnerships. In other cases, specifically in peripheral realities, urban innovation has turned out to be detached from digital infrastructures and has benefited, rather, from the social infrastructures in the area. Civic committees, community foundations, collaboration agreements between citizens and authorities, and local community development experiences developed in peripheral contexts. Regenerating urban spaces is a political objective proposed with increasing emphasis by institutional bodies at the various levels of governance. Environmental, economic, social and urban planning intersect and overlap and often projects related to urban planning "on paper" prevail over issues related to urban communities "on territories". Without adequate processes of participation and subjectivity of citizens living in urban contexts, no model of "urban renaissance" appears fully deployed, resulting in participatory processes that - at best - only allow for access logics in a neoliberal perspective. Through a qualitative methodology, the paper aims at presenting and investigating six case studies in major Italian cities (Rome, Naples, Milan, Turin, Florence, Reggio Calabria), in which democratic innovation and experimentation in civic engagement spread from the social capital of citizens and social organizations of the peripheral territory, with its specificities and its problems, In particular, the objective of the paper is to discuss and problematise the processes of participation involving and featuring vulnerable people within the reconfiguration of urban and digital spaces. Following Sutton and Kemp's approach, we consider the relationship between urban spaces and marginal communities as central to a one-to-one relationship, fostering processes of urban inclusion. Combining participatory processes in liminal marginalized communities with an institutional push towards holistic urban regeneration may develop opportunities for active citizenship, overcoming the neoliberal paradigm of the city.